Prospective biomechanical evaluation of donor site morbidity after radial forearm free flap. Issue 2 (February 2016) - Riecke, Björn; Kohlmeier, Carsten; Assaf, Alexandre T.; Wikner, Johannes; Drabik, Anna; Catalá-Lehnen, Philip; Heiland, Max; Rendenbach, Carsten
Abstract: Although the radial forearm free flap (RFF) is a commonly-used microvascular flap for orofacial reconstruction, we are aware of few prospective biomechanical studies of the donor site. We have therefore evaluated the donor site morbidity biomechanically of 30 consecutive RFF for orofacial reconstruction preoperatively and three months postoperatively. This included the Mayo wrist score, the Disabilities of the Arm, Shoulder and Hand (DASH) score, grip strength, followed by tip pinch, key pinch, palmar pinch, and range of movement of the wrist. Primary defects were all closed with local full-thickness skin grafts from the donor site forearm, thereby circumventing the need for a second defect. Postoperative functional results showed that there was a reduction in hand strength measured by (grip strength: -24.1%, in tip pinch: -23.3%, in key pinch: -16.5, and in palmar pinch: -19.3%); and wrist movement measured by extension (active=14.3% / passive= -11.5%) and flexion = -14.8% / -8.9%), and radial (-9.8% / -9.8%) and ulnar (-11.0% / -9.3%) abduction. The Mayo wrist score was reduced by 9.4 points (-12.9%) and the DASH score increased by 16.1 points (+35.5%) compared with the same forearm preoperatively. The local skin graft resulted in a robust wound cover with a good functional result. Our results show that the reduction in hand strength and wrist movement after harvest of a RFF is objectively evaluable, and did not reflect the subjectively noticed extent and restrictions in activities of daily living. Use of a local skin graft avoids a second donor site and the disadvantages of a split-thickness skin graft.